2022
DOI: 10.1038/s41467-022-31717-2
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-derived heterogeneous structural color films

Abstract: Structural colors have a demonstrated value in constructing various functional materials. Efforts in this area are devoted to developing stratagem for generating heterogeneous structurally colored materials with new architectures and functions. Here, inspired by icing process in nature and ice-templating technologies, we present freeze-derived heterogeneous structural color hydrogels with multiscale structural and functional features. We find that the space-occupying effect of ice crystals is helpful for tunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…First, to investigate the influence of LiCl content on freeze resistance, ionic hydrogels were settled in −20 °C environment for 48 h. It could be found that the ionic hydrogels without LiCl were frozen completely, while the ionic hydrogels with the 2:1 ratio of LiCl/PVA retained their original transparency, indicating excellent antifrozen capability (Figure S8). To further evaluate freeze resistance of SCIHP, a frog-shaped SCIHP was placed on a cooling plate, 36 and the optical and electrical variations were recorded and discussed (Figure S9). It could be found that when the temperature cooled to −20 °C, the structural color of the frogshaped SCIHP remained unchangeable, which was in accordance with reflection peaks results (Figure S10a).…”
Section: Resultsmentioning
confidence: 99%
“…First, to investigate the influence of LiCl content on freeze resistance, ionic hydrogels were settled in −20 °C environment for 48 h. It could be found that the ionic hydrogels without LiCl were frozen completely, while the ionic hydrogels with the 2:1 ratio of LiCl/PVA retained their original transparency, indicating excellent antifrozen capability (Figure S8). To further evaluate freeze resistance of SCIHP, a frog-shaped SCIHP was placed on a cooling plate, 36 and the optical and electrical variations were recorded and discussed (Figure S9). It could be found that when the temperature cooled to −20 °C, the structural color of the frogshaped SCIHP remained unchangeable, which was in accordance with reflection peaks results (Figure S10a).…”
Section: Resultsmentioning
confidence: 99%
“…Ice crystals grow in the polymer solution in a set direction during freezing. When polymers are cross-linked and melted, the removed ice crystals form interconnected anisotropic macro-channels within cryogels [ 119 , 120 , 121 , 122 ]. Anisotropic cryogels supported better cell migration and tissue infiltration than cryogels with randomly distributed pores [ 31 , 123 ].…”
Section: Preparation Technology Of Macroporous Hydrogelsmentioning
confidence: 99%
“…Furthermore, bioinspired, living, structurally colored soft actuators were reported by assembling engineered cardiomyocyte tissues onto synthetic inverse opal hydrogels, where autonomous shape and color regulation capability was enabled by the cell contraction and elongation in the beating processes of the cardiomyocytes [15]. Compared to chemically colored soft actuators loaded with dyes or pigments [16][17][18][19], physically colored (structurally colored) soft actuators integrated with photonic crystals display brilliant colors that are dynamically tunable by adjusting the lattice constant or refractive index and never fade as long as the periodic structures persist [20][21][22][23][24][25]. However, the structural color of soft actuators reported thus far is dependent on the viewing and light illumination angles, which is one of the critical limitations compared with chemically colored soft actuators.…”
Section: Introductionmentioning
confidence: 99%